Effects of Heat-Treatment on the Microstructure, Electromagnetic Wave Absorbing Properties, and Mechanical Properties of SiCN Fibers - Long, Xin; Zhang, Shuai; Shao, Changwei; Wang, Bing; Wang, Yingde (Frontiers in Materials, 2020)
SiCN fibers can not only be used for reinforcement of composites materials but also for electromagnetic wave (EMW) absorbing applications in high-temperature oxidizing environment above 1200℃. In this work, the microstructural evolution and EMW absorbing properties of SiCN fibers after annealing at 1300 1600℃ in N2 atmosphere were investigated. Results showed that the amorphous SiCN fibers presented poor EMW absorbing properties when the annealing temperature was below 1400℃. As the annealing temperature increased to 1500℃, the EMW absorbing properties could been largely enhanced with the minimum reflation loss value of -55.8dB and the effective absorption bandwidth value of 2.5GHz. The enhanced EMW absorbing properties should be contributed to the formation and growth of grain boundaries and defects among the amorphous fiber matrix and turbostratic graphite carbon, which could enhance the space charge polarization at the heterogeneous interfaces and increased the conductivity of SiCN fibers. Meanwhile, SiCN fibers remained a rather high tensile strength of 1.0GPa after annealing at 1500℃, which showed promising candidates for reinforcing the stealth ceramic matrix composites used in harsh environment.